2019
DOI: 10.1083/jcb.201903017
|View full text |Cite
|
Sign up to set email alerts
|

IPO11 mediates βcatenin nuclear import in a subset of colorectal cancers

Abstract: Activation of Wnt signaling entails βcatenin protein stabilization and translocation to the nucleus to regulate context-specific transcriptional programs. The majority of colorectal cancers (CRCs) initiate following APC mutations, resulting in Wnt ligand—independent stabilization and nuclear accumulation of βcatenin. The mechanisms underlying βcatenin nucleocytoplasmic shuttling remain incompletely defined. Using a novel, positive selection, functional genomic strategy, DEADPOOL, we performed a genome-wide CRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 49 publications
3
26
0
Order By: Relevance
“…During the preparation of the manuscript, a report showing that Ipo11 mediates βcatenin nuclear import in some colorectal cancers has been published, indicating that Ipo11 is required for Wnt/βcatenin activation and that Ipo11 might belong to a group of oncogenes [31]. As a result, Ipo11 must have diverse roles even in opposite according to the context on the cell death and survival, and there are a lot to be revealed for understanding the full scope of Ipo11 activity.…”
Section: Discussionmentioning
confidence: 99%
“…During the preparation of the manuscript, a report showing that Ipo11 mediates βcatenin nuclear import in some colorectal cancers has been published, indicating that Ipo11 is required for Wnt/βcatenin activation and that Ipo11 might belong to a group of oncogenes [31]. As a result, Ipo11 must have diverse roles even in opposite according to the context on the cell death and survival, and there are a lot to be revealed for understanding the full scope of Ipo11 activity.…”
Section: Discussionmentioning
confidence: 99%
“…as a factor required for beta-catenin transport 50 . Regardless of the exact mechanisms enabling NUP93 to control beta-catenin import, our promoter-reporter assays indicated that NUP93 more strongly regulates the beta-catenin pathway, as compared to other pathways.…”
Section: Discussionmentioning
confidence: 99%
“…However, the NLS identi ed in DLX3 was shown to be su cient for nuclear localization [31] and our study found that DLX3 can be imported by IPO7. Two kinds of ways may help DLX3 maintain its biological activity: passive diffusion of DLX3 to the nucleus may be su cient for regular cell activity; however, the requirements of high level of DLX3 in nucleus during the odontogenic differentiation of mDPCs may need additional DLX3 nuclear import provided by an active IPO7 mediated process [33]. In addition to NLSs, many cargos recognized by IPO7 have the speci c structures such as the proline-rich homeodomain [34], zinc ngers [35], the PAS domain [36], the leucine zipper domain [37,38] and the phosphorylated domain [39].…”
Section: Discussionmentioning
confidence: 99%